Analysis Of Actions By Jember’s Content Creators After The New Monetization Rules - Win Bernadien; Mawardi Purbo Sanjoyo (heritage, 2022)
ABSTRACT The Youtube application is rapidly expanding and changing how Indonesians enjoy the media. The increasing public interest in the existence of Youtube is shown by the growing number of content creators, known as Youtubers and Youtubers themselves. So the exciting thing to study is how Youtubers maintain their existence on Youtube, both socially and economically, because it is undeniable that humans want to exist in the social environment (Homo Homini Socius) and the economic environment (Homo economics). This study uses a qualitative method that presents a social perspective to understand the phenomenon of the research subject. The results of this research are the social and economic existence of Youtubers can be seen from the content created before or after the new Youtube Partner Program (YPP). Tepe46 and Abdikos are Youtubers from Jember who have similarities in maintaining their identity and social existence. However, it is different in maintaining economic reality, where Abdikos takes practical actions while Tepe46 tends to be instrumental. This was done because they saw the track record of their Youtube viewers and monestations. ABSTRAK Saat ini aplikasi Youtube dengan cepat merambah dan mengubah cara orang Indonesia dalam menikmati media. Meningkatnya animo masyarakat akan eksistensi Youtube ditunjukkan dengan jumlah content creator atau yang dikenal dengan istilah Youtuber dan penikmat Youtube sendiri yang semakin besar. Maka hal yang menarik untuk dikaji yaitu bagaimana kemudian para Youtuber mempertahankan eksistensinya di Youtube, baik dalam eksistensi sosial dan ekonomi. Karena tidak dapat dipungkiri manusia ingin eksis dalam lingkungan sosial (Homo Homini Socius) dan lingkungan ekonomi (Homo Ekconomicus). Dalam penelitian ini menggunakan metode kualitatif yang menyajikan prespektif sosial guna memahami fenomena dari subjek penelitian. Adapun hasil dari penelitian ini adalah eksistensi sosial dan ekonomi para Youtuber dapat dilihat dari konten yang dibuat baik sebelum atau sesudah baru Youtube Partner Program (YPP). Tepe46 dan Abdikos adalah Youtuber asal Jember yang memiliki kesamaan dalam menjaga identitas dan eksistensi sosialnya. Namun berbeda dalam menjaga eksistensi ekonomi, di mana Abdikos melakukan tindakan afektif sedangkan Tepe46 cenderung instrumentalis. Hal tersebut dilakukan karena melihat rekam jejak viewers dan monestasi Youtube mereka.